The Negative Impact of Fatherless According to Ahmad Mustafa Al-Maraghi: An Analytical Study In the Interpretation of Surah Luqman 12-19 - Akbar, A Fadly Rahman; Munawar, Ali Mahfuz; Mufida, Syafira Hasna; Nadhiya, Syarifah (Universitas Muhammadiyah Surakarta, 2025)
The phenomenon of fatherlessness or the absence of fathers in children's lives is increasing due to social and cultural changes, having a significant impact on children's moral, psychological and social development. In this context, Surah Luqman verses 12-19, as interpreted by Ahmad Mustafa Al-Maraghi, provides moral and spiritual guidance that can help children face this challenge. This study aims to analyze how the moral values in Surah Luqman can be applied to overcome the impact of fatherlessness on children. Using the literature review method and descriptive-analytical analysis, this research explores the meaning of the verses and relates them to the problem of fatherlessness faced by children in modern life. The results show that the values in Surah Luqman verses 12-19 are very relevant in shaping the personality of children who grow up without a father figure. These values include gratitude to Allah (Verse 12), strengthening monotheism (Verse 13), respecting mothers (Verse 14), prioritizing parents (Verse 15), awareness of the consequences of actions (Verse 16), discipline in prayer (Verse 17), and humility and patience (Verses 18-19). These values can help children deal with the psychological, social, and emotional challenges of fatherlessness, while building a strong moral foundation in their lives. This research recommends the development of a Qur'anic values-based education module to be implemented in families, schools and communities, as well as an empirical study to test its effectiveness in the lives of children who experience fatherlessness.